Désindustrialisation et sites Seveso : danger partout, risque nulle part ? - Samuel Rufat (Territoire en Mouvement, 2014)
After the AZF disaster in Toulouse in 2001, debates have crystallized on the alternative of moving the cities or closing the factories. Hence, the underlying trend towards deindustrialisation could appear as an easy way to reduce industrial risks. This paper examines the effects of industrialization on industrial risk by using the case of Bucharest, Romania. Bucharest, capital of Romania of 2 million inhabitants, hosts 14 Seveso sites, some of which are located near the city center. Since the mid-1990s, the share of industrial employment was divided by three and former industrial areas have been converted into shopping centers and offices. But is the industrial risk really gone? Is it rather a resorption or denial of risk? And is industrialization keeping in the background the issues of industrial risk? These questions require to articulate the monitoring of legislative and regulatory framework with a fieldwork, by comparing the discourses and practices of actors, politicians, planners, experts and residents. This articulation mobilizes qualitative and quantitative materials, with a regulation monitoring, qualitative interviews with local stakeholders (25 interviews), and a survey representative of the population of Bucharest (625 questionnaires) on the representations of risk and environment. The results indicate that deindustrialisation is not conducive to the memory of risk and the skills expertise safekeeping. It seems to impede the emergence of a culture of risk and the implementation of environmental governance and risk. Deindustrialisation then leads to an odd consensus among residents, planners, experts and elected representatives to make industrial risk management an exterior injunction without any real foundation.